Simplifying the measurement of gastric accommodation using SPECT. Issue 6 (17th February 2013) - Vijayvargiya, P.; Camilleri, M.; Shin, A.; Breen, M.; Burton, D.
Abstract Background Non‐invasive single photon emission computed tomography (SPECT) has been validated as a test for postprandial gastric volume accommodation, with volumes measured twice over 30 min and averaged. The purpose of this study is to simplify the SPECT measurement of gastric accommodation. Methods The primary aim of this study was to compare two postprandial gastric volume measurements with data collected retrospectively from 443 patients and healthy volunteers who had undergone SPECT in the last decade. The differences in the two gastric volumes were compared in the entire group and each subgroup, and the correlation between the two measurements and their differences across a wide range of gastric volumes were plotted. Key Results There was a median difference of <2% (P = 0.041) between postprandial scan 1 (757 mL) and scan 2 (743 mL), with significant correlation (rs = 0.859, P < 0.01) and excellent agreement (SD 60 mL) between the two scans across the entire range of observed postprandial gastric volumes. Conclusions & Inferences A single postprandial scan can detect gastric accommodation with the same accuracy as averaging two postprandial scans. These data support simplifying SPECT measurement of postprandial gastric volume with a scan in the first 15 min after a meal.